2015
DOI: 10.1002/masy.201550302
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Processing of Polymers for Medical and Pharmaceutical Applications

Abstract: Summary: The use of ionizing radiation for the preparation of polymeric biomaterials is one of the examples of the application of atomic energy for the benefit of humanity. Radiation processing is based on the use of high energy ionizing radiation to induce chemical and biological changes in irradiated systems. High energy electron (EB) under 10 keV and gamma irradiation are the most frequently used of ionizing radiation for synthesis, modification of polymers, and sterilization of medical devices. Potential b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Despite the fact that other studies with chitosan/poly(vinylpyrrolidone) using various ways had been reported [11,12] the gamma radiation has several advantages over more conventional technologies: it is a simple, clean and repeatable process; almost any polymer can be used and the degree of advance of the reaction can be easily controlled [13]. In comparison with chemical or photo-induced methods, radiation does not require heating of the system (allowing the use of very sensitive monomers) and does not introduce other species in the process as initiators or photo-sensitizers most of them potentially harmful for human health [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that other studies with chitosan/poly(vinylpyrrolidone) using various ways had been reported [11,12] the gamma radiation has several advantages over more conventional technologies: it is a simple, clean and repeatable process; almost any polymer can be used and the degree of advance of the reaction can be easily controlled [13]. In comparison with chemical or photo-induced methods, radiation does not require heating of the system (allowing the use of very sensitive monomers) and does not introduce other species in the process as initiators or photo-sensitizers most of them potentially harmful for human health [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, results evidenced that there was no significant degradation of chitosan in samples irradiated at 15 kGy, since the peak at 1558 cm −1 slightly increased in intensity. On the other hand, an increase in peak intensity was also observed at 1410 cm −1 , suggesting the occurrence of a chemical bond between chitosan and PVA, as well as an increase in the level of crosslinking with the increase in radiation dose [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of this technology, which does not use harmful initiators or solvents, represents a significant improvement in the current tissue engineering field. By allowing the tailoring of molecular structure, surface roughness, and porosity, ionizing radiation processing is an effective way of preparing, functionalizing, and sterilizing new materials [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels have complex polymeric networks that can keep the water inside the open spaces between the polymeric chains. The prepared hydrogel has characteristic benefits: not toxic nature, sterile, water intake of about 80%, better adhesion to the wound, and ease to remove from wound place ( Darwis et al, 2015 ). In another example, hydrogels are used in stimuli-responsive materials, hybrid organs, and implants.…”
Section: High Performance Applicationsmentioning
confidence: 99%